Extracellular DNA filaments associated with surface polysaccharide II give Clostridioides difficile biofilm matrix a network-like structure - Tania Kamwouo; Sylvie Bouttier; Séverine Domenichini; Johanna Saunier; Héloïse Coullon; Alexis Simons; Claire Janoir (npj Biofilms and Microbiomes)
Abstract Clostridioides difficile is an anaerobic, spore-forming, Gram-positive bacterium, and a leading cause of healthcare-associated intestinal infections. Recurrences occur frequently, most of them being relapses. Apart from spores, C. difficile biofilm is hypothesized as a reservoir for relapses. Thus, increased knowledge on in vitro biofilm formation and characteristics is required. We finely characterized the matrix components in 4 C. difficile strains. Confocal microscopy revealed for the first time the presence of eDNA filaments connecting bacteria, with a spider’s web-like organization. Biofilm disruption with DNase I suggests that eDNA, even in low abundance, plays a key role in the biofilm scaffold, maintaining biofilm cohesion by connecting bacteria. Observation of strong overlapping staining, particularly in the highest biofilm-producing strain tested between eDNA and polysaccharide II or lipoprotein CD1687, suggests that interactions between these components may enhance biofilm cohesion. Whereas autolysis does not appear to be a major way of matrix component release under our conditions, eDNA was sometimes associated with lipidic round shapes that can evoke vesicle structures. Together, these results suggest that the bacterial aggregation and structuring of the C. difficile biofilm involve several components of the matrix, including eDNA, interacting with each other to build the scaffold of biofilm.